Genetic analysis of endangered species Crested Ibis (Nipponia nippon) microsatellite markers - Kim, Da Hye; Kim, Yi Seul; Seo, Joo Hee; Kim, Sung Jin; Kong, Hong Sik (The Korean Journal of Ornithology, 2018)
The Korean Crested ibis Nipponia Nippon is an endangered species. A pair of Crested ibis was introduced from China in October 2008, and a successful program of artificial incubation of the species, and over 200 animals have been successfully bred through the restoration project up to 2017 at Upo ibis restoration center. We assessed genetic diversity and sex determination in the Korean Crested ibis. In total, 228 Crested ibis (115 females and 113 males) were identified. And genetic diversity measures, observed heterozygosity, expected heterozygosity, and polymorphic information content values were lower in 2017 than those in 2016. The inbreeding coefficient showed that the degree of ancestry increased in 2017. The decrease in polymorphism and increase in the degree of ancestry is thought to be due to inbreeding in such a small group. In this study provided important insight into protocols for genetic management of the breeding population of Korean Crested ibis in Korea and will help in extending the restoration program. KCI Citation Count: 1